2022
DOI: 10.3390/ijerph19148425
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Attachment and Child Health (ATTACHTM) Parenting Program on Parent-Infant Attachment, Parental Reflective Function, and Parental Depression

Abstract: High-risk families exposed to toxic stressors such as family violence, depression, addiction, and poverty, have shown greater difficulty in parenting young children. In this study, we examined the effectiveness of ATTACHTM, a 10–12 session manualized one-on-one parental Reflective Function (RF)-based parenting program designed for high-risk families. Outcomes of parent-child attachment and parental RF were assessed via the Strange Situation Procedure (SSP) and Reflective Function Scale (RFS), respectively. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 73 publications
(192 reference statements)
1
8
0
Order By: Relevance
“…The ATTACH TM intervention is a brief parenting psycho-educational intervention with dyadic (mother/primary caregiver and infant) and triadic (mother/primary caregiver, infant, and co-parenting support person) components that foster parental RF [ 26 , 45 , 89 ]. The intervention is designed to help parents enhance and develop their capacity for RF (or mentalizing).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The ATTACH TM intervention is a brief parenting psycho-educational intervention with dyadic (mother/primary caregiver and infant) and triadic (mother/primary caregiver, infant, and co-parenting support person) components that foster parental RF [ 26 , 45 , 89 ]. The intervention is designed to help parents enhance and develop their capacity for RF (or mentalizing).…”
Section: Methodsmentioning
confidence: 99%
“…A recent systemic review [ 36 ] of dyadic interventions targeting improvement in parental RF reported a significant reduction in disorganized attachment in infants (risk ratio: 0.50; 95% CI [0.27, 0.90]) [ 36 ]. Parental RF interventions also improved RF for mothers experiencing addiction [ 27 , 37 , 38 , 39 , 40 ], imprisonment [ 42 , 43 , 44 ], depression, family violence, and/or poverty [ 11 , 26 , 45 ]. Despite variations in intervention design, sample size, and coding methods for assessing parental RF, RF interventions appear to enhance maternal RF in high-risk families [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The influences of parent wellbeing on the parent–child dyad [ 1 , 2 , 3 ] and early child development [ 4 , 5 , 6 ] have been explored extensively in the general population. The most commonly researched parent wellbeing indicators include parental depression [ 7 ], trauma [ 8 ], problem gambling [ 9 ], and parental stress [ 10 ].…”
Section: Introductionmentioning
confidence: 99%